D01 Quantification Of Huntingtin Species In Huntington's Disease Patient Leukocytes Using Electrochemiluminescence Immunoassays. (17th September 2014) - Hensman, DJ; Wild, EJ; Robertson, N; Farmer, RE; Scahil, RI; Haider, S; Tessari, MA; Flynn, G; Fischer, DF; Macdonald, D; Tabrizi, SJ
Abstract : Background: Quantification of mutant and wild-type Huntingtin (HTT) and their cleaved or truncated species in living Huntington's disease (HD) patients is challenging but desirable, with the potential to assist in measuring disease progression objectively and illuminating the pathobiology of HD. Aims: Explore the nature of the soluble HTT proteins detected in HD patient samples with a series of novel, immunoassays developed for the Meso Scale electrochemiluminescence platform (PLoS One. 2014 9(5):e96854). Investigate the relationship between HTT protein and disease stage, burden and brain imaging measures. Methods: In 104 subjects (32 controls, 30 premanifest HTT-expansion carriers, 26 early and 16 moderate HD patients) we collected blood and quantified HTT protein species in mixed peripheral blood mononuclear cell pellets. Antibody combinations designed to detect total, mutant, N-terminal, mid-region and C-terminal HTT proteins were used. Between stage differences in HTT levels were analysed using linear regression, adjusted for age and gender. Associations with disease burden were analysed with and without adjusting for CAG repeats. A linear mixed model was used to estimate assay reliability. Results: Analysis of HTT protein levels across groups indicates that soluble mHTT in leukocytes is robustly detected in mutation carriers but not controls, with a signal that tends to increase with advancing disease. mHTT level was significantly associated with disease burden score. Longitudinal analysis, and associations with imaging measures are underway and will be presented at the meeting. Conclusions: This assay provides a reproducible read out of mutant HTT protein in easily accessible tissue which correlates with disease trajectory.